(untitled) (The Pretoria Student Law Review, 2021)
The argument which will be advanced in this article is that African children would benefit from accessing schools which offer them an education infused with recreational activity, through the creation of space and time for recreational activity within the school day. To this end, it will be suggested that crafting curricula which include recreational activity, specifically in the form of dance, will assist to improve the quality of education available to African children. It is argued that this proposed curriculum is a move towards the provision of the quality education demanded by the African Committee of Experts on the Rights and Welfare of the Child (ACERWC) in its Agenda 2040 for Children’s Rights in Africa (Agenda 2040).14 In order to do this, this article will first explore the content of article 11, which relates to the right to education. Thereafter, it will move to unpack the meaning of article 12, which deals with the right to recreational activity, as well as its implications. This article will then give a short account of the links between these provisions, within the context of the best interests of the child. Finally, the paper will conclude with a summary of its formulation, particularly within the context of Agenda 2040.